2013
DOI: 10.1002/ijc.28381
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti‐inflammatory drugs suppress cancer stem cells via inhibiting PTGS2 (cyclooxygenase 2) and NOTCH/HES1 and activating PPARG in colorectal cancer

Abstract: Cancer stem cells (CSCs) play a pivotal role in cancer relapse or metastasis. We investigated the CSC-suppressing effect of nonsteroidal anti-inflammatory drugs (NSAIDs) and the relevant mechanisms in colorectal cancer. We measured the effect of NSAIDs on CSC populations in Caco-2 or SW620 cells using colosphere formation and flow cytometric analysis of PROM1 (CD133) 1 CD44 1 cells after indomethacin treatment with/without prostaglandin E2 (PGE2) or peroxisome proliferator-activated receptor c (PPARG) antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 49 publications
4
73
1
1
Order By: Relevance
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin may affect apoptosis through prostaglandin-dependent or prostaglandin-independent pathways (44). In prostaglandin-dependent pathways, the inhibition of COX, particularly COX-2, is the primary mechan is minvolved in CRC suppression by aspirin (8)(9)(10)(11). COX-2 is undetectable in the normal epithelium, but is detectable in >80% of patients with CRC and is associated with larger tumor size and deeper tissue invasion (45).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other types of malignant tumors, CRC is relatively sensitive to aspirin treatment, as revealed by several independent clinical trials (5-7). A number of studies have also demonstrated that COX-2 inhibition is an important strategy for the chemopreventive treatment of colon-associated disorders (8)(9)(10)(11), resulting in a lower risk of cancer. The inhibition of COX-2-dependent signaling pathways is one mechanism involved in the good tumor-suppressive efficacy of aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…Moon и соавт. [19] провели исследование механиз-мов действия НПВС. Авторы установили супрессивное влияние НПВС на стволовые опухолевые клетки, от-ветственные за рецидивы и генерализацию опухолево-го процесса.…”
Section: Abstract: Nonsteroidal Anti-inflammatory Drugs Cyclooxygenaunclassified